No quarantine, is it safe to travel? - Susilowati, Christin; Anggraeni, Rila; Rohman, Fatchur (International Journal of Tourism and Hospitality in Asia Pasific, 2023)
ABSTRACTOne of the sectors most affected by the Covid-19 pandemic is tourism, especially because of the quarantine policy. The quarantine policy is considered an effective strategy to prevent and control the transmission of COVID-19. Quarantine refers to efforts to identify exposure to Covid-19 in a person by segregating and restricting movement. The public hope that the tourism sector will soon improve with the elimination of the quarantine policy. The removal of the quarantine policy as a form of leeway is considered to be able to increase people's intention to travel and boost economic recovery. However, some experts argue that this policy is less effective because people still have concerns over the unexpected emergence of new variants of Covid-19. This explanatory study aims to analyze the perception of quarantine elimination effect on attitude and travel intentions. The study used a survey as the data collection method. The results showed that perceived risk negatively affects tourists' attitudes toward quarantine elimination policies and travel intentions. The tourism provider need to comprehend tourist perceived risk and capable to give valuable information to reduce the risk perception.